Sensitivity analysis of using solar cells in regional electricity power supply of off-grid power systems in Iran. Issue 6 (11th May 2020) - Jahangiri, Mehdi; Haghani, Ahmad; Heidarian, Shahram; Mostafaeipour, Ali; Raiesi, Heidar Ali; Alidadi Shamsabadi, Akbar
Abstract : Purpose: Rural areas are one of the effective regions in economy and self-sufficiency field especially in agricultural and livestock section. Planning in the rural section and the effort in solving the problems of farmers lead to increase their interest in farming and manufacturing in the villages and decrease their migration to the cities and metropolitans. Therefore, the present study aimed at feasibility of electricity to a rural household in Iran using off-grid solar-based hybrid system. Design/methodology/approach: In renewable energy projects, a successful evaluation requires suitable criteria so that one can properly analyze the operational behavior of all feasible scenarios. In the present paper, HOMER software has been used for this purpose for a village with no access to electricity grid (Bar Aftab-e Jalaleh, Iran). Due to drastic fluctuation of fossil fuel prices and varied solar radiations in various years because of climate change, sensitivity analysis has been performed using HOMER. Findings: In the optimum status economically, 70% of needed energy is provided by solar cells at the price 0.792 /kWh. The comparison between the optimum condition economically and the condition that only use fossil fuels revealed that the return on investment will occur after less than 2 years and have remained profitable over 23 years. Social implications: The authors hope that the results of this study can be used in planning of the authorities to realize the interests of people in this village. Originality/value: According to the surveys, despite Iran being the first country in terms of providing solar power to the villages, so far no socio-economic-environmental assessment has been done for a solar cell-based micro-grid in an off-grid mode for a remote village that is deprived of electricity from a national electricity grid. In addition, for the first time in Iran, the effect of the fuel price and solar radiation parameters variability on the performance of system have been investigated.